2011
DOI: 10.1002/ijc.26374
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy potentiates the antitumor effect of the multikinase inhibitor sorafenib in hepatocellular carcinoma

Abstract: Multikinase inhibitor sorafenib inhibits proliferation and angiogenesis of tumors by suppressing the Raf/MEK/ERK signaling pathway and VEGF receptor tyrosine kinase. It significantly prolongs median survival of patients with advanced hepatocellular carcinoma (HCC) but the response is disease-stabilizing and cytostatic rather than one of tumor regression. To examine the mechanisms underlying the relative resistance in HCC, we investigated the role of autophagy, an evolutionarily conserved selfdigestion pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(204 citation statements)
references
References 36 publications
11
192
1
Order By: Relevance
“…Even with the same concentration of sorafenib, another study showed that autophagy protected against sorafenib-induced cell death (20). Here, we have demonstrated that sorafenib at 10 mmol/L activated autophagy, which played a protective role against cell death of parental HCC cells, and is in agreement with a previous report (21); but exhibited a death-promoting role in sorafenib-resistant HCC cells. Autophagy induced by vorinostat, a histone deacetylase inhibitor that has been approved for treating cutaneous T-cell lymphoma in clinic (41), protected against cell death independent of mTOR in vorinostat-resistant lymphoma cells (42).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even with the same concentration of sorafenib, another study showed that autophagy protected against sorafenib-induced cell death (20). Here, we have demonstrated that sorafenib at 10 mmol/L activated autophagy, which played a protective role against cell death of parental HCC cells, and is in agreement with a previous report (21); but exhibited a death-promoting role in sorafenib-resistant HCC cells. Autophagy induced by vorinostat, a histone deacetylase inhibitor that has been approved for treating cutaneous T-cell lymphoma in clinic (41), protected against cell death independent of mTOR in vorinostat-resistant lymphoma cells (42).…”
Section: Discussionsupporting
confidence: 92%
“…Autophagy induced by vorinostat, a histone deacetylase inhibitor that has been approved for treating cutaneous T-cell lymphoma in clinic (41), protected against cell death independent of mTOR in vorinostat-resistant lymphoma cells (42). The autophagic pathway crosstalks with both the caspase-dependent and -independent apoptotic pathways (13,21,43). Sustained drug exposure could induce imbalanced apoptotic pathways, leading to the resistance to apoptosis (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Chloroquine has been used in combination with many chemotherapeutic agents and a large number of trials are ongoing on its effect on cancer therapy alone or in various combinations. 83 …”
Section: Targeting Autophagy In Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Oridonin can also induce prostate cancer PC-3 cells ACD (Ye et al, 2012). In contrary, the administration of multikinase inhibitor sorafenib promotes the autophagosome formation and increases the probability of the hepatoma cells survival, suggesting that complementary strategies are urgently needed to expand the clinical application of sorafenib (Shimizu et al, 2012). For example, BO-1051, an N-mustard linked with a DNA-affinic molecule, has been reported to induce apoptosis and autophagy in hepatocellular carcinoma.…”
Section: Targeting Anoikis Resistance and Autophagy In Cancer Therapymentioning
confidence: 99%